An??lise dos crit??rios do consumidor da classe C diante da perspectiva econ??mica quanto ?? n??o compra de autom??veis chineses - Gervasoni, Viviane Chunques (2014)
The central purpose of this thesis was to find criteria to justify not buying by Chinese consumers Class C motor companies, taking into account social, instrumental and affective factors grounded theory by the country effect. To this answered the following research problem: What are the criteria used in the not buying Chinese cars for consumers in Class C decision? Accordingly, studies on consumer behavior, reasons for buying a car and the country of origin effect were considered in this study. The study of Chinese enterprises was also used in order to reach the proposed goal, to know how to analyze what are the criteria that lead the consumer class C to not buy a Chinese car, namely aspects: social, instrumental and affective. Five focus groups were conducted, and in each group there were 8 people. The whole process was recorded on audio for later analysis. The sample was selected by convenience and not probabilistic, because people in the class C more accessible to the researcher were selected by judgment of the same, since the objective was to understand the reasons which lead people class C not to buy Chinese cars. Thus, the sample was homogeneous, composed of people who bought cars in the years 2013 , 2012 and 2011, and of varied brands . Thus, this study can be briefly defined in its qualitative research method as inductive qualitative approach, using as tools: a case study, phenomenology and focus groups to understand the phenomenon embraced. The nature of this research can be classified as exploratory, it aims to provide greater awareness of the problem, namely criteria that lead to C - class consumers do not buy Chinese cars. Data collection took place through interviews of focus groups, where the technique of analysis employed was content analysis. A test was conducted to determine if there was sufficient consistency in the codes that emerged . This was accomplished by checking the same for three different researchers. The results suggested that social class does not gain momentum in consumer choice of class to buy Chinese brand cars and is located - at the stage of pre purchase and that is influenced by the country of origin of automobile manufacturing. Other categories also emerged in this study attested that the reasons why the consumer does not buy class C of Chinese brand automobiles, namely, instrumental and affective reasons , these are set out in detail in this study .